Literature Analysis on Active Learning Models as an Alternative to the Dominance of Lecture Methods in Public Elementary Schools - Tamsik Udin; Sehan Rifky Arfanaldy (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The lecture method is still the dominant approach in learning in Public Elementary Schools (SDN) in Indonesia, although it has weaknesses in increasing student engagement and developing critical thinking skills. This study aims to analyze the effectiveness of active learning models as an alternative to the dominance of the lecture method and to identify obstacles in its implementation. The method used in this study is a literature study that analyzes various previous studies related to active learning in SDN. The study results indicate that the lecture method was chosen because of time efficiency, limited resources, and lack of teacher understanding of active learning models. However, Cooperative Learning, Problem-Based Learning (PBL), and Inquiry-Based Learning have proven more effective in improving student learning outcomes and their analytical and collaborative skills. The main obstacles in implementing active learning include teacher readiness, lack of facilities, cultural resistance from the community, and curriculum policies that are still oriented towards academic values. This study recommends intensive teacher training, improving learning facilities, and changing the paradigm in the education system to support the implementation of active learning in SDN. With the right strategy, active learning models can be applied more widely to improve the quality of basic education in Indonesia.